A model of assessment and intervention for Non-Verbal Learning Disability (NVLD) in the Australian education system: an educational and developmental psychologist perspective. Issue 1 (2nd January 2018) - Brenchley, Celia; Costello, Shane
Abstract: Non-Verbal Learning Disabilities (NVLD) have a relatively rare incidence, estimated to be approximately 1.7% of all learning disabilities. Symptoms of the disorder are perceptual, social and emotional. These symptoms differ according to the developmental age, with 85% of cases being diagnosed in secondary school when education becomes more complex. In Australia the intricate arrangements between funding for intervention within the school and the requirements from the assessment authority in each state for special provision mean that a cohesive model is required for school professionals to guide education for NVLD students. This is particularly important to enable access to tertiary education. A flow-chart model of assessment and intervention for the Australian education system is demonstrated, which draws on two case studies ("Katie" currently attending university and "Jamie" currently in year 8) with the provision of Australian and International research and literature to validate the model.